THE Analysis of The Relationship Between Crude Palm Oil (CPO) Prices and Stock Prices of Issuers of The Palm Oil Plantation Group in 2023 - Situmorang, Roni Patar; Manurung, Marlinang I.C (Journal of E-business and Management Science, 2024)
Crude palm oil (CPO) is an important commodity in the industrial and food world. This oil is obtained through an extraction process from the flesh of the oil palm fruit. CPO has a variety of uses in various sectors. CPO is used in the food and beverage industry, such as margarine, cooking oil, and processed food products. In addition, it is also used in the production of biodiesel as an alternative environmentally friendly fuel. In the cosmetics industry, it is used in the manufacture of soap and other skincare products. The chemical industry also utilizes CPO as a raw material in producing various products, including detergents. With the great potential and advantages of CPO, oil palm plantations in Indonesia have a very important role in the world economy and even place Indonesia as the largest producer and supplier of CPO. Geographical support and a large land area can produce the highest production volume in the world. The law of supply and demand for CPO affects the share price of issuers of the Large Private Plantation group listed on the Indonesia Stock Exchange. This study was conducted to determine whether there is a relationship between fluctuations in CPO prices and fluctuations in issuers' stock prices. There are two issuers that become the object of this research, namely PT Astra Agro Lestari Tbk (code AALI) and PT Sinar Mas Agro Resources and Technology Tbk (code SMAR).